Effects of Sambiloto (Andrographis paniculata) on GLP-1 and DPP-4 Concentrations between Normal and Prediabetic Subjects: A Crossover Study. (15th January 2022) - Tarigan, Tri Juli Edi; Purwaningsih, Erni Hernawati; Yusra,; Abdullah, Murdani; Nafrialdi,; Prihartono, Joedo; Saraswati, Made Ratna; Subekti, Imam
Abstract : Background . The extract of Andrographis paniculata (Burm. F.) Wall. Ex. Nees. (sambiloto) (穿心蓮 chuān xīn lián) has been reported to have an antidiabetic effect on mice models and has been used traditionally in the community. The exact mechanism of sambiloto extract in decreasing plasma glucose is unclear, so we investigated the role of sambiloto extract in the incretin pathway in healthy and prediabetic subjects. Methods . This study was a randomized, placebo-controlled, crossover, double-blind trial. It included 38 people who were healthy and 35 people who had prediabetes. All subjects were randomly assigned to receive either the intervention sambiloto extract or a placebo. All subjects were randomly assigned to receive the first intervention for 14 days. There was a washout period between subsequent interventions. The primary outcome was glucagon-like peptide 1 (GLP-1) concentration, and secondary outcomes were fasting insulin, 2-hour postprandial insulin, homeostasis model assessment of insulin resistance (HOMA-IR), fasting blood glucose, 2-hour postprandial blood glucose, dipeptidyl peptidase-4 (DPP-4), and glycated albumin before and after the intervention. Result . After the intervention, GLP-1 concentration significantly increased in prediabetes by 19.6% compared to the placebo (p = 0.043 ). There were no significant differences in the changes of fasting insulin, 2-hour postprandial insulin, HOMA-IR, fasting blood glucose, 2-hour postprandial blood glucose, DPP-4, and glycated albumin levels after the intervention. Sambiloto extract did not inhibit the DPP-4 enzyme in healthy and prediabetic subjects. Conclusion . Sambiloto extract increased GLP-1 concentration without inhibiting the DPP-4 enzyme in prediabetic subjects. This trial is registered with ClinicalTrials.gov (ID: NCT03455049 ), registered on 6 March 2018—retrospectively registered (https://clinicaltrials.gov/ct2/show/NCT03455049 ).